Grain boundary engineered, multilayer graphene incorporated LaCoO3 composites with enhanced thermoelectric properties. Issue 17 (1st September 2022) - Davis, Nithya; R, Althaf; Muraleedharan, Sreepriya; Thiruvenkatam, Vijayaraghavan; Mayandi, Jeyanthinath; Finstad, Terje G.; Razanau, Ihar; Novikau, Uladzimir; Ashok, Anuradha M.
Abstract: Enhancement of thermoelectric properties by virtue of decreased electrical resistance through grain boundary engineering is realised in this study. A robust strategy of optimisation of the transport properties by tuning the energy filtering effects at the interfaces by decreasing the interfacial electrical resistance is achieved in LaCoO3 (LCO). This is accomplished by the incorporation of multilayer graphene within the parent LCO matrix containing multi-scale nano/micro grains. The present work has attained a substantial increment in electrical conductivity from a value of 96 Scm -1 for bare LCO to ∼5300 Scm -1 at 750 K by incorporating 0.08 wt% multilayer graphene in LCO. No significant change in thermal conductivity is observed due to the presence of multilayer graphene in LCO. A zT of 0.33 at 550 K for 0.08 wt% multi-layer graphene incorporated LCO composite is achieved which is the highest thermoelectric figure of merit value for undoped LCO reported until now.